ANALYSIS OF CRIMINAL LIABILITY OF THE HEAD OF THE MARKETING SECTION AT BANK SUMUT WHO COMMITTED CORRUPTION IN THE DECISION OF THE MEDAN DISTRICT COURT NUMBER 67/PID.SUS-TPK/2025/PN MDN - Amran Effendi Dalimunthe; Muhammad Hizbullah (CV. Barokah Publsiher, 2026)
Based on the results of the study, it shows that the application of the elements of criminal acts of corruption in providing credit that does not comply with Banking Standard Operating Procedures in the Medan District Court Decision Number 67 / Pid.Sus-TPK / 2025 / PN Mdn is appropriate because the panel of judges has stated that the charges of Article 3 of Law No. 31 of 1999 have been fulfilled based on written evidence, witness testimony evidence, and the defendant's statement. The form of unlawful acts committed by the Head of the Marketing Section so that it is qualified as a criminal act of corruption in Decision Number 67 is the defendant's actions in not carrying out the credit analysis process in accordance with applicable provisions, approving applications for 2 credit facilities with incorrect data. The defendant's punishment is imprisonment for 1 year and 4 months and a fine of Rp. 50,000,000.